Heavy metal sensors and sequestrating agents based on polyaromatic copolymers and hydrogels. Issue 1 (19th August 2020) - Alwattar, Aula A; Haddad, Athir; Moore, Joshua; Alshareef, Mubark; Bartlam, Cian; Woodward, Adam W; Natrajan, Louise S; Yeates, Stephen G; Quayle, Peter
Abstract: A series of readily available, amphiphilic pyrene‐ and perylene‐containing fluorescent materials, derived from the co‐polymerisation of 2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid with acrylate esters, can be used to detect heavy metal ions in the micromolar concentration range in aqueous solutions. The incorporation of these amphiphilic copolymers into semi‐interpenetrating hydrogels also resulted in the irreversible removal of divalent Co 2+, Ni 2+, Cu 2+ and Pb 2+ ions from aqueous solutions at neutral pH. Abstract : A scalable synthesis of amphiphilic, fluorescent, acrylate–2‐acrylamido‐2‐methyl‐1‐propanesulfonic acid copolymers and hydrogels affords materials that behave as sensors and irreversible sequestrating agents for heavy metals.